Increasing Organizational Commitment through Learning Organization, Serving Leadership, Personality, and Job Satisfaction - Solihatun, Solihatun; Retnowati, Rita; Laihad, Griet Helena (Journal of Social Research, 2023)
This study aims to find strategies and ways to increase commitment to the organization. This research method uses quantitative methods with path analysis techniques and SITEREM (Scientific Identification Theory to Conduct Operations Research in Education Management) analysis. The total population in this study was 265 teachers and the sample was 159 permanent teachers of private junior high school foundations in Depok, West Java. The strategy for increasing commitment to the organization is through strengthening the learning organization, servant leadership, personality, and job satisfaction. The way to improve each variable is to improve weak indicators and maintain strong indicators. Furthermore, the results of the hypothesis in this study include: there is a positive and significant direct effect. Based on the results of the SITEREM analysis, the priority order of indicators that need to be addressed is 1) Listening, 2) Wages and Salaries, 3) Promotion, 4) Sense of belonging to the School, 5) Amount of Income Earned, 6) Reciprocity Get from School. The novelty of this research is a study at a private junior high school in Depok, West Java, which is an educational institution that applies Colquitt's theory and strategies for achieving organizational commitment. Furthermore, the implication in efforts to increase commitment to the organization is that it is necessary to strengthen the Learning Organization, strengthen service leadership, strengthen personality, and strengthen job satisfaction.